Pengembangan Potensi Sumber Daya Alam Di Desa Ulak Pandan Kabupaten Ogan Komering Ulu - Angga Wibowo Gultom Gultom (LPPM Universitas HKBP Nommensen, 2020)
Each region certainly has natural resources that can be used by the community to be processed and used as a source of income. Good natural resources are not sold raw but must be processed and made into a product so that the economic value of these natural resources are high. Based on rules, one of the elements in charge of cultivating and developing natural resource potentials to have high value is the village. Villages have a very important role in determining how to manage their resources. Villages that are active and creative will maximize the potential of their natural resources to bring economic value and welfare of their citizens. The emergence of independent villages and developed villages started from a correct understanding of their natural potential resources and began to process them appropriately and well planned. For this reason, this community service activity is carried out, in order to increase the understanding and open the mindset of the apparatus and villagers on how to develop the natural potential resources in their village. This community service activity is carried out by means of presentation and discussion methods taking place in the village hall. The results of this service will conclude what potential the ulak pandan village has and how to make the ulak pandan village develop their natural potential resources with the hope that the ulak pandan village can become a more advanced village in the future.